Urban green spaces and public health: legal challenges and policy opportunities in green city governance - Guo, Yuanyuan; Wu, Dan; Zuo, Xiangbin (Frontiers in Public Health, 2025)
With the increasingly prominent impact of urban green space reduction on publichealth, this study selects three typical cities (Beijing, Hangzhou, and Yinchuan) toexplore the relationship between green space coverage and residents’ health, aiming to address challenges in green city governance and identify policy opportunities. Using multi-source data including remote sensing images, health statistics, and legal texts, combined with methods such as spatial econometric models and legal text analysis (Policy Strength Index, PSI), the study evaluates green space distribution, quantifies health benefits, and assesses policy effectiveness. The results show that there is a nonlinear threshold relationship between green space coverage and health benefits: when the coverage rate exceeds 38%, the decline rate of chronic diseases is significantly accelerated by 3.3 times, and the improvement rate of mental health reaches 9.7%. Among the three cities, Hangzhou achieves the most notable results with its “Park City” policy, featuring an average annual green space growth rate of 1.8% (far higher than Beijing’s 0.6% and Yinchuan’s -0.3%) and a leading PSI score of 82 points (significantly higher than Yinchuan’s 58 points). Further analysis reveals that policy implementation effectiveness depends on three core factors: legal strength, departmental coordination, and public participation. Based on these empirical findings, this study suggests adopting a trinity governance path of “accurate greening-system reconstruction-fair promotion” to drive the transformation and upgrading of urban green governance models, providing empirical support for building healthy, equitable, and sustainable urban environments.